The toxic impact of local anaesthetics in menopausal women: causes, prevention and treatment after local anaesthetic overdose. Local anaesthetic systemic toxicity syndrome - Sobolewski, Bogusław; Doman, Paweł; Stetkiewicz, Tomasz; Oszukowski, Przemysław; Woźniak, Piotr (Menopause Review/Przegląd Menopauzalny, 2015)
Gynaecologists often use local anaesthetics in their medical practice. Some concomitant diseases during the menopausal period may cause problems during the qualification of postmenopausal women for general anaesthesia in gynaecological surgery. Many authors suggest the application of local analgesia for particular kinds of gynaecological surgery procedures performed on postmenopausal women, taking into consideration health determinants. While applying local anaesthetics, the possibility of their overdose has to be taken into account. Generalised toxic symptoms which appeared after the local anaesthesia are rare, but potentially are lethal complications. Toxic symptoms after local anaesthetic administration are manifested after accidental administration of a medicine into a blood vessel, when extravascular administration of a large volume of a local anaesthetic is absorbed into a bloodstream or with the reproducible doses of local anaesthetics which are administered when metabolism does not work sufficiently and cannot eliminate these substances. Clinical overdose of local anaesthetics is manifested by disorders in two systems. Firstly, the pathological symptoms come from the central nervous system (CNS). In the second phase, the pathological symptoms will additionally appear in the cardiovascular system. The aim of the present thesis is to remind clinical manifestations of the local anaesthetic overdose and suggest the management of patients with the aforementioned symptoms, especially in the case of intravenous lipid emulsions which have the status of an antidote in life-threatening conditions caused by cardiotoxic effects of local anaesthetics.